2016
DOI: 10.1021/acscatal.5b02062
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Depolymerization with Nitrate-Intercalated Hydrotalcite Catalysts

Abstract: Hydrotalcites (HTCs) exhibit multiple adjustable parameters to tune catalytic activity, including interlayer anion composition, metal hydroxide layer composition, and catalyst preparation methods. Here, we report the influence of several of these parameters on β-O-4 bond scission in a lignin model dimer, 2-phenoxy-1-phenethanol (PE), to yield phenol and acetophenone. We find that the presence of both basic and NO 3 − anions in the interlayer increases the catalyst activity by 2−3fold. In contrast, other anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 81 publications
1
55
0
3
Order By: Relevance
“…Nevertheless, big difficulties in the catalytic processing of this biomass fraction due to the existence of a variety of different interunit linkages, high affinity for the formation of a more condensed structure when thermochemically processed, poor product selectivity, and easy use as a solid fuel are the major barriers towards the development of lignin-based biorefining technologies. 217 220 This study demonstrated that the LDH-catalyst characterized by the simultaneous presence of OH − and NO 3 2− anions in the interlayer space can be as active as the Ni-supported material (Ni/HT). Although the role of the NO 3 − species in the catalytic process is still not totally understood, three main conclusions were presented for these types of catalysts: first, the nitrate is acting heterogeneously, as no significant catalytic activity was observed in the presence of homogeneous Ni 2+ , NO 3 − and CO 3 2− species; second, the presence of nitrates favors the accessibility to the basic sites of the hydrotalcite, i.e.…”
Section: Lignin Depolymerizationmentioning
confidence: 77%
“…Nevertheless, big difficulties in the catalytic processing of this biomass fraction due to the existence of a variety of different interunit linkages, high affinity for the formation of a more condensed structure when thermochemically processed, poor product selectivity, and easy use as a solid fuel are the major barriers towards the development of lignin-based biorefining technologies. 217 220 This study demonstrated that the LDH-catalyst characterized by the simultaneous presence of OH − and NO 3 2− anions in the interlayer space can be as active as the Ni-supported material (Ni/HT). Although the role of the NO 3 − species in the catalytic process is still not totally understood, three main conclusions were presented for these types of catalysts: first, the nitrate is acting heterogeneously, as no significant catalytic activity was observed in the presence of homogeneous Ni 2+ , NO 3 − and CO 3 2− species; second, the presence of nitrates favors the accessibility to the basic sites of the hydrotalcite, i.e.…”
Section: Lignin Depolymerizationmentioning
confidence: 77%
“…Catalytic properties of nickel hydrotalcites are strongly influenced by the nature of interlayer anion. The presence of NO 3 -anions, or other basic anions, such as OH -and CO 3 2-, in the interlayers conferred up to a three-fold activity enhancement in the depolymerisation of the model lignin compound 2-phenoxy-1-phenethanol [71], wherein acetophenone (and phenol) were the principal products. Although the origin of this base promotion remains unclear, the depolymerisation mechanism may involve direct nitration of the phenolic.…”
Section: Base-catalyzed Depolymerizationmentioning
confidence: 99%
“…HT addition on R3 had no significant effect, the degradation profile and methane yield of both remained the same. Kruger et al (2016) found that anions in the HT interlayers enhanced the catalytic activity of lignin depolymerization however they also reported no effect in different samples. Through extensive literature review no conclusive proof was found that could link the inefficiency of the HT in R3 with its lignin concentration.…”
Section: Effect Of Hydrotalcite Additionmentioning
confidence: 95%
“…Hydrotalcites (HTs) are anionic clays that have been used in a wide range of applications because of the possibility of designing them tailored to specific reactions and/or substrates. In recent years they have been studied in the treatment of various industrial wastewaters, as they can tackle different contaminants in water due to their high ionexchange capacities for adsorption (Wajima, 2014) and are able to depolymerize lignin (Kruger et al, 2016). HTs have also been proven to increase hydrogen production in fermentation processes (Wimonsong et al, 2014) and methane production in anaerobic digestion (Rodriguez-Chiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%